Evaluation of Offshore Shiftwork using Heart Rate Variability. (September 2017) - Shortz, Ashley E.; Franke, Madeline; Kilic, E. Simay; Peres, S. Camille; Mehta, Ranjana K.
The high fatality rate in oil and gas extraction (OGE) is a growing concern within the industry. OGE workers are exposed to long work hours, intense mental and physical workload, coupled with changing shift patterns, which can lead to elevated fatigue levels. The aim of this study was to explore the effect of shiftwork on heart rate variability indicators of workload and fatigue using wearable monitors in offshore operations. Ten male operators (age: 31.3 (6.1) years; stature: 1.72 (0.1) m; weight: 85.24 (9.8) kg) were monitored throughout their daily shifts for six days on an offshore drillship using physiological sensors. Heart rate variability (HRV) was measured in the frequency (ratio of low to high frequency; LF/HF) and temporal (root mean square of successive differences; RMSSD) domains. Six of the ten operators underwent swing shifts in the middle of the data collection period. There was a main effect of shift time on HRV parameters (i.e., operators on night shift were in a more fatigued state), and a main effect of swing shift on LF/HF (i.e., when swing shift occurred, those operators were more fatigued). Findings suggest that physiological profiles differ based on shift time and swing shifts, and that swing shifts for night shift workers adversely affect heart rate variability responses.